2018
DOI: 10.4103/jcd.jcd_112_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cleaning protocols on bond strength of etch-and-rinse adhesive system to dentin

Abstract: Aim:This study aimed to evaluate the cleaning protocol of dentin impregnated with epoxy resin-based sealer (AH Plus) and the effects on the adhesive interface using 95% ethanol (E) or formamide solution (F) associated with microabrasion with glass microparticles (M).Methodology:Forty dentin specimens were impregnated with sealer (AH Plus). Specimens were cleansed according to the following protocols (n = 10): G1 (E); G2 (F); G3 (E = M); and G4 (F = M). No treatment was performed in G5 (control). Specimens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Scanning electron microscopy (SEM) is often used to observe sealer residues and requires specimen processing, such as spraying gold and a vacuum environment. 10 , 11 , 12 , 13 In the present study, a real-time noninvasive SS-OCT imaging technique was used to evaluate trapped sealer remnants in the dentin-adhesive interface. 24 OCT technology has been used in several clinical applications, such as monitoring the internal adaptation of resin composite restoration and cariogenic demineralization and detecting tooth cracks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Scanning electron microscopy (SEM) is often used to observe sealer residues and requires specimen processing, such as spraying gold and a vacuum environment. 10 , 11 , 12 , 13 In the present study, a real-time noninvasive SS-OCT imaging technique was used to evaluate trapped sealer remnants in the dentin-adhesive interface. 24 OCT technology has been used in several clinical applications, such as monitoring the internal adaptation of resin composite restoration and cariogenic demineralization and detecting tooth cracks.…”
Section: Discussionmentioning
confidence: 99%
“…During the last two decades, there have been 10 published in vitro studies on sealer removal, with different cleaning methods proposed. 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Dry cotton pellets and organic solvents were mostly studied, followed by mechanical drill refinement, air polishing, microabrasion. It has been found that after cleaning using dry cotton pellets, the bond strength decreased to 69%–88% to that of uncontaminated controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, acid etching was reported as a promising strategy to remove the smear layer of root dentin,[ 24 ] since it provides open dentinal tubules and consequently better adhesion between the adhesive system and the dentin. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%